Development and evaluation of an antigen targeting lateral flow test for Crimean-Congo Haemorrhagic FeverResearch in context - Caitlin R. Thompson; Ilkay Bozkurt; Yasemin Cosgun; Patricia Blundell; Annelyse Duvoix; Michael Johnson; Hakan Hedef; Fatma Gonca Arslan; Busra Ayyildiz Umudum; Heval Can Bilek; Esra Tanyel; Ayşe Nur Pektaş; et al. (EBioMedicine)
Summary: Background: Crimean-Congo Haemorrhagic Fever (CCHF) is a viral haemorrhagic fever with a case fatality rate of 5–25% that has been prioritised for research and development by the World Health Organisation. There are no CCHF rapid diagnostic tests (RDTs) commercially available. We describe the development and evaluation of an antigen-targeting lateral flow immunoassay RDT for CCHF. Methods: Prospective clinical samples were collected and tested between July and October 2023 in Türkiye. Retrospective stored samples were obtained from the Central Public Health Laboratory, Baghdad, Iraq. The sensitivity and specificity of the CCHF RDT was compared to reverse transcription quantitative polymerase chain reaction assays. Findings: On prospective clinical samples in Türkiye, the sensitivity and specificity of the CCHF RDT was 90.4% [95% CI 81.5–95.3%] (n = 73) and 96.2% [95% CI 87.0–99.3%] (n = 52), respectively with a sensitivity of 92.9% [95% CI 84.3–96.9%] (n = 70) in samples with a cycle threshold (Ct) ≤30. On retrospective stored samples in Iraq, sensitivity and specificity of the RDT was 71.7% [95% CI 59.2–81.5%] (n = 60) and 92.5% [95% CI 80.1–97.8%] (n = 40), respectively with a sensitivity of 82.2% [95% CI 68.7–90.7%] (n = 45) in samples of Ct ≤30. Interpretation: The CCHF RDT was an effective rapid diagnostic test in this preliminary clinical evaluation, showing this RDT has the potential diagnostic capability for use at the point-of-care. Definitive evaluation is now required to ensure the RDT meets the regulatory requirements for commercialisation. Funding: The Liverpool School of Tropical Medicine, National Institute for Health Research Health Protection Research Unit in Emerging Zoonotic Infections, The Medical Research Council and The Pandemic Institute.